Исследование эффективности противовоспалительной композиции и препарата «Тантум Верде®» в комплексной терапии генерализованного пародонтита - Борисенко, Анатолій Васильович; Куваєв, О. С.; Столяр, В. Г.; Мялківський, К. О. (Actual Dentistry, 2020)
Objectives. Periodontal disease is the most widespread human diseases. The problem of rational treatment of generalized periodontitis is actual. In the complex treatment of patients with generalized periodontitis widely used antiinflammatory medicaments. Among them is well-known nonsteroidal antiinflammatory drugs (NSAID) Tantum Verde® (benzydamine hydrochloride). Investigation of antiinflammatory activity of drug compositions based on medicinal plants and preparation Tantum Verde® was made. Aim. The determination of the clinical efficacy of the proposed pharmaceutical compositions and well-known drug Tantum Verde® in the initial stage of complex treatment of generalized periodontitis. Materials and methods. Clinical investigation was conducted in two groups of patients. The first consisted of 30 patients with generalized periodontitis, the second – 30 similar patients, who underwent dental implants. Mtdicamental treatment was carried out using a pharmaceutical composition of the proposed solution and rinse Tantum Verde®. For this purpose, the patients of both groups were divided into two groups: the first used pharmacological composition, the second – Tantum Verde® rinsing solution. Patients were conducted a comprehensive examenation of periodontal tissue before treatment and after treatment. To evaluate the clinical efficacy of treatment used Schiller-Pisarev test (1962), the index of PMA by C. Parma (1961), hygienic index by Fedorov-Volodkina (1978), the vacuum test by Kulazhenko (1961). Results. As a result of the investigation it was found that the usage of the proposed pharmaceutical composition in the complex therapy of patients with generalized periodontitis can effectively inhibit the dystrophic-inflammatory process in periodontal tissues. This confirms by the decline in the index PMA, increase the time of formation of hematoma during the vacuum tests on Kulazhenko, improving oral hygiene. Conclusions. Application of the proposed pharmaceutical composition increases the effectiveness of treatment of patients with generalized periodontitis. Key words: generalized periodontitis, pharmacological composition, Tantum Verde®.